PENINGKATAN HASIL BELAJAR IPA DENGAN MENGGUNAKAN METODE EKSPERIMEN PADA POKOK BAHASAN KARYA BERTEKNOLOGI SEDERHANA PADA SISWA KELAS IVA SDN 010 BAYUR SAMARINDA UTARA TAHUN PEMBELAJARAN 2016/2017 - Afdal Afdal; Nur Agus Salim (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2017)
The experimental method is where students practice, try, see and prove for themselves the work or something they learn.This research can be said PTK (classroom action research) used to know improvement of learning result IPA by using experimental method on the subject of simple tech work on the students of grade IVA SDN 010 BayurSamarinda Utara Learning Year 2016/2017. After teachers or researchers apply experimental methods. This research was conducted on Wednesday 8 February 2017 and the research was completed on Friday 17 February 2017 the number of students as the object of research as many as 30 students. This research was conducted in two cycles one cycle has 4 stages: planning stage, implementation stage, observation stage, and reflection stage. Each end of the cycle is given a test to determine student learning outcomes. Preliminary data is taken from the pre-cycle beginning done before cycle I begins. While the final data obtained at the end of each cycle after the test. The collected data is analyzed quantitatively and qualitatively, using the frequency table, and the mean score, and setting the level of learning result category. The benchmark indicator of the success of this study is if 75% of students have obtained a minimum score of 70 from the final test results then the class is considered complete.